IMPLEMENTASI STRATEGI PEMBELAJARAN REACT DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Arfandi Arfandi; Siti Zulaeha; Kandiri Kandiri (LP2M Universitas Ibrahimy, 2022)
Based on the results of the average daily test, the material in PAI lessons has not met the KKM. In addition, teachers at these schools tend to use conventional models in PAI learning and rarely relate the material taught to students' real lives or phenomena that occur, so students do not understand what the teacher is saying and become passive in learning activities.The monotonous learning process often makes students bored to follow it. So far, what is widely known in the learning process has not made students happy in learning because they still use less varied methods, namely the lecture method, question and answer and assignments. The main problems in this research are as follows: (1) How is the application of the REACT learning strategy in PAI. and (2) How is the improvement of student learning outcomes through the application of REACT learning strategies in PAIBP. In this study using the type of classroom action research. The object of this research is SMP Negeri 1 Kendit. In this study used various kinds of data collection, namely observation, interview and documentation. Based on the results of the discussion and findings, it can be concluded as follows: 1) The application of the REACT learning strategy PAI, that all components are implemented in accordance with the steps with the aim of being effective in learning, and 2) There is an increase in student learning outcomes from pre-cycle reaching 55%, increasing 14% in the first cycle to 69% then implementing the second cycle, increasing 21% so that it reaches 90% through the implementation of learning strategies REACT PAIBP.